Nanosecond pulsed electric field incorporation technique to predict molecular mechanisms of teratogenicity and developmental toxicity of estradiol‐17β on medaka embryos. Issue 5 (27th December 2017) - Yamaguchi, Akemi; Ishibashi, Hiroshi; Kono, Susumu; Iida, Midori; Uchida, Masaya; Arizono, Koji; Tominaga, Nobuaki
Abstract: Herein, we propose using a nanosecond pulsed electric field (nsPEF) technique to assess teratogenicity and embryonic developmental toxicity of estradiol‐17β (E2 ) and predict the molecular mechanisms of teratogenicity and embryonic developmental defects caused by E2 on medaka ( Oryzias latipes ). The 5 hour post‐fertilization embryos were exposed to co‐treatment with 10 μm E2 and nsPEF for 2 hours and then continuously cultured under non‐E2 and nsPEF conditions until hatching. Results documented that the time to hatching of embryos was significantly delayed in comparison to the control group and that typical abnormal embryo development, such as the delay of blood vessel formation, was observed. For DNA microarray analysis, 6 day post‐fertilization embryos that had been continuously cultured under the non‐E2 and nsPEF condition after 2 hour co‐treatments were used. DNA microarray analysis identified 542 upregulated genes and one downregulated gene in the 6 day post‐fertilization embryos. Furthermore, bioinformatic analyses using differentially expressed genes revealed that E2 exposure affected various gene ontology terms, such as response to hormone stimulus. The network analysis also documented that the estrogen receptor α in the mitogen‐activated protein kinase signaling pathway may be involved in regulating several transcription factors, such as FOX, AKT1 and epidermal growth factor receptor. These results suggest that our nsPEF technique is a powerful tool for assessing teratogenicity and embryonic developmental toxicity of E2 and predict their molecular mechanisms in medaka embryos. Abstract : We improved the nanosecond pulsed electric field treatment condition and assessed the teratogenicity and embryonic developmental toxicity of estradiol‐17β on medaka embryos. Furthermore, we analyzed gene expression profiles in embryos using DNA microarray and performed pathway and network analyses to understand the molecular mechanisms of estradiol‐17β in teratogenicity and embryonic developmental toxicity. Our findings suggested that nanosecond pulsed electric field technique is a powerful tool for assessing teratogenicity and embryonic developmental toxicity of estradiol‐17β and predict their molecular mechanisms in medaka embryos.